Mulheres com câncer de colo do útero: avaliação da qualidade de vida - FERREIRA, Thayane Costa (2020)
The present study aimed to assess the quality of life of women with cervical cancer. Descriptive-transversal research with a quantitative approach carried out with 175 women undergoing treatment for cervical cancer at the outpatient clinic of the cancer hospital Aldenora Bello. The instrument used was composed of two questionnaires: the first containing closed questions regarding the socioeconomic, demographic and clinical conditions of the patients and the second the EORTC QLQ-30. The collected data was stored in a specific database created in Microsoft Excel version 2016 program and statistical analysis was performed using the IBM SPSS 24 program. The results showed that the majority of the interviewees were between 40 and 59 years old at the time of diagnoses (56%), mixed race (69,8%), with incomplete primary education (44,7%), married (42,3%), had between 4 and 7 children (49,2%), were unemployed (40%), catholics (50,9%) and had a monthly family income of 1 to 3 minimum wages (6,9%). As for health conditions, menarche prevailed > 12 years (89,7%), first sexual intercourse < 18 years old (74,3%), 1 to 5 sexual partners (88,6%), the majority never used oral contraceptives (68,6%), non-alcoholics (96%), non-smokers (96%) and nor did practice physical activity (81,1%), the interval of days between clinical diagnosis and treatment was ≤ 60 days (76,6%). As for clinical conditions, squamous cell carcinoma (90,3%) prevailed, T3b / IIIB staging (41%) and the association between radiotherapy and chemotherapy (42,8%) as forms of treatment. Regarding the interviewees’ quality of life assessed by the global health status, it was considered satisfactory. When evaluating the quality of life averages obtained in the various domains, it was found that, in the functional scales, the items social function (84,2 ± 29,4), functional performance (62,3 ± 40,4) and physical function (61,0 ± 27,5) obtained the greatest results. On the symptom scale, financial difficulties (66,7 + 41,2) were the most common. Thefore, it is extremely importante to include measures of quality of life in clinical practice, these can be essential in the evaluation of certain therapeutic interventions and in the consequences of the disease in the lives of these women.